A Comparative Assessment of Analytical Fate and Transport Models of Organic Contaminants in Unsaturated Soils - Stoppiello, Maria Grazia; Lofrano, Giusy; Carotenuto, Maurizio; Viccione, Giacomo; Guarnaccia, Claudio; Cascini, Leonardo (Sustainability, 2020)
Analytical models for the simulation of contaminants’ fate and transport in the unsaturated zone are used in many engineering applications concerning groundwater resource management and risk assessment. As a consequence, several scientific studies dealing with the development and application of analytical solutions have been carried out. Six models have been selected and compared based on common characteristics to identify pros and cons as well as to highlight any difference in the final output. The analyzed models have been clustered into three groups according to the assumptions on contaminant source and physico-chemical mechanisms occurring during the transport. Comparative simulations were carried out with five target contaminants (Benzene, Benzo(a)pyrene, Vinyl Chloride, Trichloroethylene and Aldrin) with different decay’s coefficient, three types of soil (sand, loam and clay) and three different thicknesses of the contaminant source. The calculated concentration at a given depth in the soil for the same contamination scenario varied greatly among the models. A significant variability of the concentrations was shown due to the variation of contaminant and soil characteristics. As a general finding, the more advanced is the model, the lower the predicted concentrations; thus, models that are too simplified could lead to outcomes of some orders of magnitude greater than the advanced one.